DEVOPS MATURITY ASSESSMENT AT CAD-IT IOT CENTRE USING DEVOPS MATURITY MODEL - Rizki Maulana, Akbar
CAD-IT IoT Centre is an organization that provides Internet of Things based solutions and products. DevOps is one of the methods used by the organization to develop IoT solutions efficiently. However, the implementation of DevOps practices is accompanied by several issues. Therefore, this research aims to analyze the organization’s DevOps adoption by using DevOps Maturity Model and design strategies for improving the DevOps implementation maturity to level 5. Focus Area DevOps Maturity Model was the model used in this research. Analytical data was obtained from 47 respondents using a questionnaire. Rasch model analysis was utilized for the reliability and validity of the questionnaire data. An item reliability index of 0.9275 and person reliability index of 0.8025 as well as 61 out of 63 items having a positive point-measure correlation index indicated that the questionnaire data was reliable and generally valid. Based on the research results, the organization’s maturity level was maturity level 1 with 8 focus areas belonging the Underdeveloped category. A strategy had been designed to implement 9 capabilities that could improve the DevOps implementation maturity level to reach maturity level 5 on the Focus Area DevOps Maturity Model.